1970
DOI: 10.3758/bf03329021
|View full text |Cite
|
Sign up to set email alerts
|

History-related effects upon human escape responding: Are induction or extinction processes involved?

Abstract: consider the individual items more or less simultaneously and then divide his time among items as he sees fit. It seems reasonable to assume that when the method of stimulus presentation limits S to organizing stimulus materials along associative dimensions-as in the discrete method of stimulus presentation-he is at a distinct disadvantage in encoding a set of items with little or no inherent associative relatedness. However, when S is afforded an opportunity to consider material as a whole, where he may conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The overall picture emerging from the 3 experiments presented here, that the degree of response recovery is related to prior experimental history, has been observed in a variety of situations by other investigators. Weiner (1969Weiner ( , 1970 has shown that prior histories of fixed-ratio (FR) or differential reinforcement of low rate (DRL) schedules using positive reinforcement produce differential effects on subsequent escape and avoidance response rates and that the effects persist even after extinction of the FR and DRL responding. The present study has demonstrated the parallel case that prior history of aversive schedules can also affect subsequent behavior differentially.…”
Section: Discussionmentioning
confidence: 99%
“…The overall picture emerging from the 3 experiments presented here, that the degree of response recovery is related to prior experimental history, has been observed in a variety of situations by other investigators. Weiner (1969Weiner ( , 1970 has shown that prior histories of fixed-ratio (FR) or differential reinforcement of low rate (DRL) schedules using positive reinforcement produce differential effects on subsequent escape and avoidance response rates and that the effects persist even after extinction of the FR and DRL responding. The present study has demonstrated the parallel case that prior history of aversive schedules can also affect subsequent behavior differentially.…”
Section: Discussionmentioning
confidence: 99%